Clinical impact of PD-L1 expression in triple-negative breast cancer patients with residual tumor burden after neoadjuvant chemotherapy - Gizem Oner; Semen Önder; Hüseyin Karatay; Naziye Ak; Mustafa Tükenmez; Mahmut Müslümanoğlu; Abdullah İğci; Ahmet Dincçağ; Vahit Özmen; Adnan Aydiner; Ekrem Yavuz; Neslihan Cabioğlu (World Journal of Surgical Oncology, 2021)
Abstract Background Studies on PD-L1 expression in breast cancer have gained importance in recent years, especially in triple-negative breast cancer (TNBC). Our aim was to analyze the differential expression of PD-L1 to explore its correlation with response to neoadjuvant chemotherapy (NACT) and patient survival. Methods PD-L1 expression was evaluated immunohistochemically (Ventana SP263 clone kit) by staining tumor specimen. PD-L1 positivity was defined as membranous staining > 1%, > 5%, > 10%, and > 20% on either tumor cell (TC) and /or immune cell (IC). Results Fifty patients with locally advanced TNBC, who had a partial response to NACT, were included in the study. PD-L1 staining was observed in TCs in 25 patients (50%) and in ICs in 23 patients (46%) when PD-L1 > 1% was considered positive. Patients with PD-L1 positivity on ICs were more likely to respond to chemotherapy as measured by “MD Anderson Cancer Center Residual Cancer Burden Index” (14/22, 63.6% vs. 10/27, 37%, p = 0.064). The 5-year disease-free survival (DFS) and disease-specific survival (DSS) rates were 46.3% and 51.4%, respectively. A high (> 20%) tumoral PD-L1 positivity was associated with a better DFS and DSS. Conclusions Studies in the literature mostly focused on PD-L1 expression in inflammatory cells. However, our results suggest that patients with a high PD-L1 expression on TCs were more likely to have a better outcome. Since patients with residual tumor burden who express PD-L1 on TILs were more likely to respond to NACT, an immune checkpoint inhibitor therapy in addition to NACT would be an important option for TNBC with locally advanced disease.